2015
DOI: 10.1091/mbc.e14-11-1530
|View full text |Cite
|
Sign up to set email alerts
|

SINC, a type III secreted protein of Chlamydia psittaci, targets the inner nuclear membrane of infected cells and uninfected neighbors

Abstract: SINC, a secreted effector of Chlamydia psittaci, uniquely targets the inner nuclear membrane of infected cells and uninfected neighbors. Candidate partners include ELYS, lamin B1, and four proteins of the inner nuclear membrane, suggesting that SINC interacts with host proteins that control nuclear structure, signaling, and chromatin organization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 124 publications
2
64
1
Order By: Relevance
“…CPAF was initially described as a chlamydial protease degrading host cell transcription factors; however, its impact on virulence and pathogenicity is currently controversially discussed (20). SINC is a type III secreted protein targeting the nuclear membrane of infected cells, which may modulate the nuclear envelope function (10,11). Here, we have demonstrated that virulence-associated antibodies are generated predominantly in animals that have aborted.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…CPAF was initially described as a chlamydial protease degrading host cell transcription factors; however, its impact on virulence and pathogenicity is currently controversially discussed (20). SINC is a type III secreted protein targeting the nuclear membrane of infected cells, which may modulate the nuclear envelope function (10,11). Here, we have demonstrated that virulence-associated antibodies are generated predominantly in animals that have aborted.…”
Section: Discussionmentioning
confidence: 78%
“…From these, we have selected nine proteins for recombinant synthesis and further evaluation. These comprised (i) three surface proteins, specifically, the major outer membrane protein (MOMP), macrophage infectivity potentiator (MIP), and Pmp13G; (ii) three virulence-associated proteins, namely, the homologs of Chlamydia protease-like activity factor (CPAF), translocated actin-recruiting phosphoprotein (TARP), and secreted inner nuclear membrane-associated Chlamydia protein (SINC) (11), and (iii) three hypothetical proteins, specifically, CAB031, CAB821, and CAB408, two of which (CAB821 and CAB408) are predicted to be secreted by the type III secretion system (12). For a comprehensive analysis of the ovine and human antibody responses to these antigens, we used the so-called line immunoassay since this format allows the simultaneous detection of antibodies to multiple antigens in a single run (13).…”
mentioning
confidence: 99%
“…BioID samples were processed for mass spectrometry as outlined by (27). Briefly, streptavidin beads were washed with 50 mM NH 4 HCO 3 and resuspended in 50 mM NH 4 HCO 3 containing 5 mM dithiothreitol and heated at 75°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…When Hela cells are infected by C. psittaci, SINC incorporates into the NE of the host cell nucleus and interacts with Nups, ELYS, lamin B1, and emerin, leading to alterations in nuclear shape and function in both infected cells and neighboring uninfected cells. 194 Many diseases are associated with altered nuclear morphology, so identifying approaches to correct these morphological defects may lead to novel therapeutics.…”
Section: Nuclear Morphology and Diseasementioning
confidence: 99%